The Effect of Agitation Parameter on Hardness and Thickness of Decorative Nickel-Chrome Coating on A36 Steel using Electroplating Process - Akmal Hanif Khairullah Harsito; Iis Siti Aisyah; Daryono Daryono; Ali Saifullah; Heni Hendaryati; Sudarman Sudarman (University of Muhammadiyah Malang, 2020)
Electroplating is a process of settling substances (metal ions) on the electrodes (cathodes) using electrolysis. The occurrence of a precipitate in this process is due to the presence of electrically charged ions moving from an electrode through the electrolyte, the result of the electrolyte will seal on another electrode (cathode). During the process of deposition/deposit takes place a chemical reaction occurs at the electrode and electrolyte both reduction in a certain direction permanently, therefore it requires direct current and a constant voltage. Metal coatings commonly used are copper, nickel, chromium, and others. Electroplating is basically to coat the metal to make it look more attractive and protected from corrosion, and can increase the product's resistance to friction. The purpose of this study was to determine the effect of stirrer rpm variations on the thickness and thickness of the A36 steel layer in the decorative nickel-chrome electroplating process. 4 specimens in this study were 30x30x2 (mm). Nickel and chromium coatings have variations in the speed of 72, 102, 132, and 162 (rpm) with a time immersion of 22 minutes and with a temperature of 55-60 ° C. The results of this electroplating process were tested by Vickers's hardness test and observation of microstructure results. The results showed that the faster the rpm, the more hardness was obtained which increased and the thickness of the layer increased. The highest hardness and thickness values are found at a rotational speed of 132 rpm. With a hardness value of 77.5 VHN and a thickness value of 4.55 µm (Nickel) and 13.76 µm (Chrome).